THE INFLUENCE OF ENTREPRENEURIAL ORIENTATION AND PRODUCT INNOVATION ON BUSINESS PERFORMANCE IN BATIK MSMEs JAMBI CITYDANAU TELUK DISTRICT - M. Rapi Saputra; Ratih Kusumastuti; Derist Touriano (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to investigate the impact of entrepreneurial initiation and product development on the business performance of batik SMEs in the Danau Teluk Region of Jambi City. It adopts a quantitative research approach with a population comprising 44 batik MSMEs registered at the UKM Cooperative Office, Industry and Trade Office in Jambi Province. The study includes a sample of 44 attempts, utilizing a saturated sampling method. Data is collected through a survey, and the research employs a descriptive analysis method, including classical assumption testing and sequential multiple linear regression using SPSS version 22. The results reveal that entrepreneurial initiation significantly and positively influences business performance, while product development also has a positive and significant impact. The variable with the most dominant effect is entrepreneurial initiation. Joint testing indicates that both entrepreneurial initiation and product development collectively exert a positive and significant impact on business performance.